The ichthyofauna associated with Taylor's salt marsh, Kariega estuary (Eastern Cape), South Africa - Booth, Tara Loren (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2009)
The spatial and temporal patterns in the ichthyofaunal community composition and structure in Taylor's salt marsh and adjacent eelgrass beds (Zostera capensis) in the Kariega Estuary, was investigated every two months between May 2006 and March 2007. Total ichthyofaunal abundances and biomass in the salt marsh ranged between 0.55 and 21.7 ind.10m-2 and between 0.03 and 1.9 g.wwt.10mâ »Â², respectively. There were no significant spatial patterns in the values evident (P > 0.05 in all cases) although seasonal trends were marked, with highest values consistently recorded during the warmer summer months. Investigations into the community structure showed that the ichthyofaunal community within salt marsh was composed almost exclusively of juveniles of estuarine dependant (category II) species, mainly juvenile Mugilidae (<20mm SL) that comprised up to 83% of all fish sampled. Hierarchical cluster analysis and multidimensional scaling did not identify any distinct spatial patterns in the ichthyofaunal community within the salt marsh. The absence of any spatial patterns in the community structure could be related to the absence of any significant spatial patterns in the physico-chemical (temperature, salinity and dissolved oxygen concentrations) and biological (water column and microphytobenthic algal concentrations) variables within the salt marsh (P > 0.05 in all cases). Temporal shifts in the ichthyofaunal community structure within the salt marsh were, however, evident largely reflecting the breeding cycles of individual species within the sub-region. Within the adjacent eelgrass beds, total ichthyofaunal abundances and biomass ranged between 8.4 and 49.4 ind.10mâ »Â² and between 2.9 and 94.5 g.wwt.10mâ »Â², respectively. Once again there were no distinct spatial patterns in the abundance and biomass values evident although seasonal patterns were marked. In contrast to the salt marsh, within the in the eelgrass community, there were a large number of adult individuals recorded. Again category II species, the estuarine dependent species, were numerically and gravimetrically dominant. The dominance of category II species reflects the marine dominance of Kariega Estuary. The remaining estuarine utilisation categories did not contribute significantly to abundance or standing stock totals. Hierarchical cluster analysis showed that the salt marsh and eelgrass beds represented two distinct habitats within the Kariega Estuary. Within the salt marsh, the family Mugilidae were numerically dominant contributing 83% of the total catch. Within the eelgrass beds, the sparid, Rhabdosargus holubi and representatives of the family Gobidae contributed 36.3% and 33.9% respectively to the total catch. Estuaries with a wide range of microhabitats have been demonstrated to support a more diverse ichthyofaunal community. Shallow water habitats in general are important areas for juvenile fish within estuaries. Taylor's salt marsh provides an alternative shallow water habitat, occupied by a distinct ichthyofaunal community composition, with increased food availability and decreased predation pressure, for a wide range of fish species.
Keywords: Fishes -- South Africa -- Eastern Cape; Estuaries -- South Africa -- Eastern Cape; Fish communities -- South Africa -- Eastern Cape; Salt marsh animals -- South Africa -- Eastern Cape; Eelgrass -- South Africa -- Eastern Cape; Gray mullets -- South Africa -- Eastern Cape